2019
DOI: 10.33225/pec/19.77.528
|View full text |Cite
|
Sign up to set email alerts
|

Foundation Phase Students’ Metacognitive Abilities in Mathematics Classes: Reflective Classroom Discourse Using an Open Approach

Abstract: The research findings describe a model of experiential learning that promotes the development of foundation phase student teachers’ metacognitive abilities for mathematics through classroom reflective discourse using an open approach. A case study was carried out on two foundation phase mathematics classes in South Africa’s universities; data were collected through observation and focus group interviews. The research’s main findings indicated that student teachers’ interest in reflective classroom discourse is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Furthermore, Siyaya et al (2022) deduced interdependence between metacognitive skills and technology integration. Similarly, Tachie (2019aTachie ( , 2019b found that metacognitive skills are useful in enhancing learners' "M", in STEM, process skills and recommended that studies should focus more on finding pedagogies to integrate the teaching of metacognitive skills in STEM education. Untested evidence point out to SOLEs pedagogy as one of the incorporative pedagogical strategies that can be implemented in STEM education to enhance educational outcomes while equipping learners with 4IR skills,…”
Section: Sole Pedagogy Metacognitive Skills and Conceptual Understand...mentioning
confidence: 99%
“…Furthermore, Siyaya et al (2022) deduced interdependence between metacognitive skills and technology integration. Similarly, Tachie (2019aTachie ( , 2019b found that metacognitive skills are useful in enhancing learners' "M", in STEM, process skills and recommended that studies should focus more on finding pedagogies to integrate the teaching of metacognitive skills in STEM education. Untested evidence point out to SOLEs pedagogy as one of the incorporative pedagogical strategies that can be implemented in STEM education to enhance educational outcomes while equipping learners with 4IR skills,…”
Section: Sole Pedagogy Metacognitive Skills and Conceptual Understand...mentioning
confidence: 99%
“…If learners have understood the concept behind a particular question it is obvious the time that may be used to work for the solution will be reduced [21]. This is because the problem in a given question is already clear to learners.…”
Section: Research Questionmentioning
confidence: 99%
“…Apart from heuristic, metacognition is associated with designing, monitoring, and evaluating cognitive processes in P-S [20], [21]. Good problem solver tend to gain from personal experience and general knowledge, from being able to use analogies, and from metacognitive skills [15].…”
Section: Introductionmentioning
confidence: 99%